2006
DOI: 10.1097/01.brs.0000216593.97157.dd
|View full text |Cite
|
Sign up to set email alerts
|

Notochord Cells Regulate Intervertebral Disc Chondrocyte Proteoglycan Production and Cell Proliferation

Abstract: MD, FRCP(C) † Study Design. Non-chondrodystrophic dog notochord cell conditioned medium was used to evaluate chondrocyte proteoglycan production and cell proliferation.Objectives. To evaluate the responsiveness of bovine disc-derived chondrocytes to notochord-cell conditioned medium with respect to proteoglycan and cell proliferation. In addition, to examine phenotypic changes of notochord cells cultured in monolayered as compared to 3-dimensional culture.Summary of Background Data. Non-chondrodystrophic dogs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(118 citation statements)
references
References 39 publications
5
112
0
1
Order By: Relevance
“…The use of NCs for disc repair is attractive in view of the suggestion that they are stem cells or organizer cells for the NP (13). Implanted NCs improve repair in animal models of acute disc degeneration either directly by producing matrix (13) or indirectly by secreting soluble factors (17) that stimulate the matrix production of MNPCs (17,(47)(48)(49)(50). However, in the light of current findings, both of nutritional requirements and of sensitivity to nutrient deprivation, NCs at concentrations found in vivo may fail to survive in large degenerated human discs with limited nutrient availability ( Figure 4C); those contemplating their prospective use in disc repair should at least consider these possible limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The use of NCs for disc repair is attractive in view of the suggestion that they are stem cells or organizer cells for the NP (13). Implanted NCs improve repair in animal models of acute disc degeneration either directly by producing matrix (13) or indirectly by secreting soluble factors (17) that stimulate the matrix production of MNPCs (17,(47)(48)(49)(50). However, in the light of current findings, both of nutritional requirements and of sensitivity to nutrient deprivation, NCs at concentrations found in vivo may fail to survive in large degenerated human discs with limited nutrient availability ( Figure 4C); those contemplating their prospective use in disc repair should at least consider these possible limitations.…”
Section: Discussionmentioning
confidence: 99%
“…[5]. Is it a dose-response issue whereby the discs that are relatively deficient in notochordal cells are therefore lacking in the necessary and sufficient molecules synthesized by these cells that may act upon the NP cell [6,7]? It is thought that the notochordal cell-rich disc NP phenotype confers superior biomechanical properties [5,8].…”
mentioning
confidence: 99%
“…In fact, transformation of the matrix by cells in human discs is very slow, and studies have shown that proteoglycan turnover takes about 20 years (Roughley, 2004) and collagen turnover takes more than 100 years (Verzijl et al, 2000). However, autologous transplantation of cells with a high proteoglycan production capacity such as notochordal cells and mesenchymal stem cells may lead to successful repair of degenerated discs , Aguiar et al,1999, Cappello et al, 2006, Erwin & Inman, 2006. Even if the transplantation of cells with a high proteoglycan production capacity into the nucleus pulposus is feasible, it is also essential for preventing the progression of disc degeneration that the transplanted cells survive in the degenerated disc and continue to produce appropriate macromolecules for maintenance of disc mechanical strength throughout life.…”
Section: Which Animal Model Is Most Suitable To Study Tissue Engineermentioning
confidence: 99%
“…Aguiar et al have suggested that the notochordal cells found in the human nucleus pulposus up to approximately 10 years of age play an active role in nucleus pulposus development and in the maintenance of disc integrity through the production of soluble factors that induce nucleus pulposus cells to increase proteoglycan synthesis (Aguiar et al, 1999). Interestingly, it has been found that co-culture of immature cells such as mesenchymal stem cells with notochordal cells and adult nucleus pulposus cells (chondrocyte-like cells) stimulates proteoglycan synthesis more rapidly, and this method has been extensively used in studies on disc regeneration , Cappello et al, 2006, Erwin & Inman, 2006. However, previous studies on proteoglycan production by notochordal cells and chondrocyte-like nucleus pulposus cells have only compared proteoglycan synthesis on the basis of sulphate synthesis, and no studies have compared glycosaminoglycan accumulated by these cells.…”
Section: Metabolic Activities Of Notochordal Cells and Non-notochordamentioning
confidence: 99%